Baseline behaviour moderates movement skill intervention outcomes among young children with autism spectrum disorder. (October 2021) - Bremer, Emily; Lloyd, Meghann
This study examined whether adaptive behaviour, emotional and behavioural challenges, and social skills, respectively, moderated the effect of a movement skill intervention on movement skills among preschool aged children with autism spectrum disorder. Twenty-seven participants with autism spectrum disorder ( N = 13 experimental) between 3 and 5 years of age participated in a 12-week fundamental movement skill intervention. Movement skills were assessed at baseline and post-test. Adaptive behaviour, emotional and behavioural challenges, and social skills were assessed at baseline. A repeated-measures analysis of variance tested the group by time effect on movement skills. Three separate moderation analyses were then run to test the moderating effect of adaptive behaviour, emotional and behavioural challenges, and social skills, respectively, on the relationship between group assignment and movement skills at the post-test. The experimental group significantly improved their movement skills following the intervention ( p = 0.02, ηp2=.19). The moderation analyses showed that adaptive behaviour ( b ( SE ) = 0.86 (0.41), p < 0.05) and emotional and behavioural challenges ( b ( SE ) = −1.5 (0.8), p = 0.06) at baseline moderated the association between group and post-test movement skills, when controlling for baseline movement skills. These findings may help caregivers and clinicians individualize treatment plans in regard to movement skill interventions for preschool-aged children with autism spectrum disorder. Lay abstract: It is common for children with autism spectrum disorder to experience delays in their movement skills. These skills are important for participation in play and physical activity. Previous research has found that movement skills can be improved with movement skill interventions. This study explored the behavioural factors of young children with autism spectrum disorder that make them most likely to improve their movement skills following a 12-week intervention. The study found that children with higher levels of adaptive behaviour and lower levels of emotional and behavioural challenges at the start of the intervention were more likely to have greater improvements in their movement skills following the intervention. These findings may help clinicians and caregivers plan which types of interventions are best suited for individual children with autism spectrum disorder.